Integrating Technology into Social Work Practice and Study: Needs, Challenges, and Opportunities - Petružytė, Donata; Gevorgianienė, Violeta; Charenkova, Jūratė; Seniutis, Miroslavas; Šumskienė, Eglė; Žalimienė, Laimutė; Yamaguchi, Mai (Acta Paedagogica Vilnensia, 2023)
This article reveals the views of Japanese and Lithuanian lecturers on the need for technological development in social work and the impact such development can have on the competencies of future social work professionals. 10 qualitative semi-structured interviews were conducted with lecturers from Lithuania and 8 with lecturers from Japan. The data analysis is based on Moor’s (2008) model of technological revolution, which consists of three stages: 1) introduction stage, 2) permeation stage and 3) power stage. The paper discusses the main categories that emerged from the data analysis: types of technology and their use in social work; personal characteristics, knowledge and skills needed by future social workers to integrate technologies into their practice; and value challenges for future social workers. The study revealed that technology integration in Lithuania is still at the introduction stage. At the theoretical level, there are discussions on the possible paradigmatic changes that the introduction of technology would bring to the social work field, at the practical level there is fragmented research on the impact of technical assistance tools on the quality of services, and in the area of values and ethics, questions about the benefits, risks and challenges of using technology are being addressed. In Japan, there is a deeper integration of technology into social work practice and studies, with more technology-oriented research, the development of the practice of technology use, and consideration of ethical aspects of technology use in practice. Lecturers in both countries fear that the rapid introduction of technology will cause the social work profession to lose its image as a “relational profession”. Furthermore, there are doubts about whether technology will help social work to fulfil its mission of social justice, as the issue of affordability of expensive technology is also raised. The views of the participants reflect concerns about changes in the identity of the social work profession, as seen through the changes in the knowledge, skills and values inherent in the profession, which are generated by the integration of technology and which lead to the idea of an emerging new identity for the profession.